Upaya Pemberdayaan Ekonomi Masyarakat Melalui Badan Usaha Milik Desa (BUMDes) Gabe di Desa Sipan Kecamatan Sarudik Kabupaten Tapanuli Tengah - Judika Juniarta Nainggolan; Maringan Sinambela; Martua Sihaloho; Liyus Waruwu; Harisan Boni Firmando (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2024)
Community economic empowerment is something that is really needed by the community to improve the quality of life by managing and developing the resources and potential they have. This research aims to determine economic empowerment efforts through Gabe Village-Owned Enterprises (BUMDes) in Sipan Village, Sarudik District, Central Tapanuli Regency. This research uses descriptive qualitative research methods, the data collection methods used are observation, interviews and documentation. The results of this research show that the economic empowerment efforts carried out through BUMDes are exploring the village's potential for establishing business units, establishing 3 business units such as swimming pools, gallon business units, renting party kitchen equipment, and the final effort is recruiting workers. The driving factors in managing BUMDes are support from the government, community involvement, and natural resources and local potential. The implications of community economic empowerment through BUMDes are increasing local economic income or original village income and opening up employment opportunities for some of the Sipan village community. With efforts to empower the community's economy through BUMDes, it is hoped that it can further improve the village and community economy.